A NEW STYLE OF DEPICTION IN THE FOLKLORE WORKS OF GASHAM ISABAILI (Scientific journal of the Fergana State University, 2025)
There are sources that feed the creative ideology and products of Gasham Isabayli, and play the role of impetus in its germination and growth, development and maturation. It is necessary to mention the role of folklore among these sources.When we look not only at the creativity of Gasham Isabayli and Azerbaijani artists, but in general at the literary-ideological armory of world children's literature, we see that folklore has played the role of the most reliable and fertile source for the creativity of the most respected children's writers and poets in all nations. In other words: "Folk creativity became one of the main sources of children's literature with its high ideality and aesthetic fullness.Of course, it is not without reason that folklore plays the most important role in the development of world children's literature, and that children's artists repeatedly turn to it on a global scale. Convenient plots, mysterious language, smooth development, full characters, memorable characters, ease in events, internal dynamics, unexpected situations, abundance of artistic means of description, rich fantasy, optimistic spirit, gentle humor, etc. makes children love folk literature. As you can see, folklore has a lot of promise for children's literature with its wide and favorable possibilities. Indeed, the relationship between them is multi-characteristic, multi-signal. In general, in addition to being a great artist, the people are also great educators, and "no one can compete with the pedagogical genius of the people." The main task of children's literature is to educate the growing generation. In addition, "the people in their poetry cover the whole life, all the interests, all the activities of the child. He created the poetic laws of children's poems... The people really understood the literary taste of children in an ingenious way.In the article, the artist's creative use of styles and elements of folklore in the works of Gasham Isabayli, such as "Nanam takdi", "Akil-Bakil", "Uüü", etc., was studied.